A longitudinal examination of perinatal testosterone, estradiol and vitamin D as predictors of handedness outcomes in childhood and adolescence. Issue 6 (2nd November 2022) - Richards, Gareth; Tan, Diana Weiting; Whitehouse, Andrew J. O.; Chris McManus, I.; Beaton, Alan A.; Hickey, Martha; Maybery, Murray T.; Licari, Melissa K.; Lawson, Lauren
ABSTRACT: The developmental origins of handedness remain elusive, though very early emergence suggests individual differences manifesting in utero could play an important role. Prenatal testosterone and Vitamin D exposure are considered, yet findings and interpretations remain equivocal. We examined n = 767 offspring from a population-based pregnancy cohort (The Raine Study) for whom early biological data and childhood/adolescent handedness data were available. We tested whether 18-week maternal circulatory Vitamin D (25[OH]D), and testosterone and estradiol from umbilical cord blood sampled at birth predicted variance in direction of hand preference (right/left), along with right- and left-hand speed, and the strength and direction of relative hand skill as measured by a finger-tapping task completed at 10 (Y10) and/or 16 (Y16) years. Although higher concentrations of Vitamin D predicted more leftward and less lateralized (regardless of direction) relative hand skill profiles, taken as a whole, statistically significant findings typically did not replicate across time-point (Y10/Y16) or sex (male/female) and were rarely detected across different (bivariate/multivariate) levels of analysis. Considering the number of statistical tests and generally inconsistent findings, our results suggest that perinatal testosterone and estradiol contribute minimally, if at all, to subsequent variance in handedness. Vitamin D, however, may be of interest in future studies.